Prognostic Nutritional Index as a Predictor of Postoperative Outcome in Patients with Gastrointestinal Malignancies - Udayanilavan Padmanaban; Avinash Ramakrishnan; Abhinaya Reddy; Rajeshwari Murugesan; Chilaka Suresh; Uday Kumbhar; Ankit Jain; Sreenath Gubbi Shamanna (International Journal of Nutrition Sciences, 2025)
Background: Nutritional status of patients plays an important role in post-operative recovery. A preoperative index can help predict the post-operative morbidity and in optimizing the patient’s status. This study was done to evaluate the usefulness of prognostic nutritional index (PNI) in identifying patients who are at high risk for developing postoperative morbidity.Methods: In a retrospective study, data were collected from databases during January 2019 and December 2022 by including all patients who underwent surgery for gastrointestinal malignancies with a curative intent. Univariate and multiple logistic analyses were performed to evaluate the factors which affect the postoperative morbidity.Results: Data of 182 patients was retrieved from the database. Stomach carcinoma was the most common gastrointestinal cancer of our study. Surgical site infection was the most common complication noted among 33.5% (n=61) of patients. On univariate analysis of the factors which contributed to post-operative morbidity, PNI and American Society of Anaesthesiologists score was found to be significant in assessments. On multiple regression analysis, only PNI was found to be helpful in predicting postoperative morbidity. The area under curve for predicting the postoperative complications in our study was 0.608 (95%CI, 0.525-0.690, p=0.012). The cut-off value of PNI was 72.9 with a sensitivity and specificity of 62% and 53.3%.Conclusion: Encouraging the routine use of PNI in preoperative assessments for patients undergoing gastrointestinal cancer surgery can potentially lead to a better risk stratification, more targeted perioperative management, and ultimately improved surgical outcome.